Genetic enhancement of okra [Abelmoschus esculentus (L.) Moench] germplasm through wide hybridization - Suma, A.; Joseph John, K.; Bhat, Kangila Venkataramana; Latha, Madhavan; Lakshmi, Chakkamadathil Jayasundaran; Pitchaimuthu, Mottaiyan; Nissar, V. A. M.; Thirumalaisamy, Polavakkalipalayam Palanisamy; Pandey, Chitra Devi; Pandey, Sushil; Kumar, Ashok; Gautam, Raj Kumar; et al. (Frontiers in Plant Science, 2023)
The introgression of genetic material from one species to another through wide hybridization and repeated back-crossing, plays an important role in genetic modification and enriching the cultivated gene-pool. Okra (Abelmoschus esculentus [(L.) Moench)] is a popular vegetable crop with high dietary fibre and protein, rich in essential amino acids, lysine and tryptophan. The wild Abelmoschus genepool has many desirable traits like ornamental value, short internodal length, more number of productive branches, extended bearing, perennation tendency, reduced fruit length, high mucilage content, abiotic stress tolerances like drought, high temperature and biotic stress resistances such as Okra Yellow Vein Mosaic Virus (OYVMV) and Okra Enation Leaf Curl Virus (OELCV) diseases. The repeated use of elite breeding lines has led to narrowing of the genetic base of the okra crop which is one of the major factors related to breakdown of resistance/tolerance to biotic stresses. Hence, wide hybridization was attempted to transfer tolerant genes from wild species to cultivated genepool using the wild Abelmoschus species found tolerant (Abelmoschus pungens var. mizoramensis, A. enbeepeegeearensis, A. caillei, A. tetraphyllus and A. angulosus var. grandiflorus) in natural epiphytotic conditions. The 113 cross derivatives generated [F1 generation (30), F3 (14), one each in F2 and F4 generations, back cross generation in BC1F2 (03), BC1F3 (25), and BC2F2 (02), crosses between amphidiploids (27), multi-cross combinations (07) and inter-specific cross between A. sagittifolius × A. moschatus subsp. moschatus) selfed derivatives at F8 generation (03)] were characterized in the present study, besides advancing the generations through selfing and backcrossing. The amphidiploids were found to possess many desirable genes with a considerable magnitude of linkage drag. Majority of the wide cross derivatives had an intermediate fruit morphology and dominance of wild characters viz., hispid fruits, stem, leaves, tough fruit fibre, vigorous perennial growth habit and prolonged flowering and fruiting. The fruit morphology of three BC progenies exhibited a high morphological resemblance to the cultivated okra, confirming successful transfer of useful genes to the cultivated okra genepool. The detailed morphological characteristics of the various combinations of Abelmoschus amphidiploids and the genetic enhancement of the genepool achieved in this process is reported here.